(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study examines speech act learning as part of pragmatic studies in Indonesian language learning through the application of role-playing methods. The background of this study stems from the condition of Indonesian language learning in schools, which still tends to emphasise internal aspects of language, such as structure and linguistic rules, so that students’ communicative abilities in real contexts have not developed optimally. The purpose of this study is to describe the urgency of teaching speech acts and the effectiveness of role-playing methods in improving students’ pragmatic competence. This study uses a qualitative descriptive method with a literature review approach to various theoretical sources and relevant previous research results. The results of the study show that speech act learning plays an important role in helping students understand the meaning of speech contextually and increasing their awareness of the principles of politeness in language. The role-playing method is considered effective because it provides opportunities for students to practise speech acts in communication situations that resemble real-life conditions. Thus, speech act learning through the role-playing method not only improves communicative language skills but also contributes to the development of empathy, social awareness, and polite character in communication.